UPAYA PENINGKATAN PENGEMBANGAN BAHASA METODE FIELD TRIP KUNJUNGAN KE SAWAH - Ili Suharti; Vivi Anggraini; Dadan Suryana; Setiyo Utoyo (STKIP Subang, 2026)
This research is motivated by the low language development of children aged 5–6 years at Hawari Islamic Kindergarten, Tanjung Ganti I Village, Kaur Regency. Based on initial observations, most children still experience difficulties in constructing descriptive sentences, expressing ideas or opinions, answering simple questions, demonstrating courage to speak, and retelling experiences orally. This study aims to improve the language development of children aged 5–6 years through a field trip to a rice field. This study used the Classroom Action Research (CAR) method with the Kemmis and McTaggart model, implemented in two cycles, including planning, implementation, observation, and reflection. The study subjects were 10 children in Group B at Hawari Islamic Kindergarten, Tanjung Ganti I Village, Kelam Tengah District, Kaur Regency in 2026. Data collection techniques were carried out through observation and documentation. Data were analyzed using quantitative descriptive techniques by calculating the percentage of achievement of children's language development indicators. The results of the study showed that the average child's language development increased in each cycle, from 22% in the pre-cycle, to 48% in Cycle I, and reaching 80% in Cycle II. Improvements occurred in the ability to construct descriptive sentences, express ideas or opinions, answer simple questions, speak confidently, and tell stories. Thus, the field trip method to the rice fields has proven effective in improving the language development of children aged 5–6 years at Hawari Islamic Kindergarten, Tanjung Ganti I Village, Kaur Regency.